Out of the darkness and into the light: bright field in situ hybridisation for delineation of ERBB2 (HER2) status in breast carcinoma. Issue 3 (4th March 2010) - Gruver, Aaron M; Peerwani, Ziad; Tubbs, Raymond R
Abstract : Assessment of ERBB2 ( HER2) status in breast carcinomas has become critical in determining response to the humanised monoclonal antibody trastuzumab. The current joint College of American Pathologists and the American Society of Clinical Oncology guidelines for the evaluation of HER2 status in breast carcinoma involve testing by immunohistochemistry and fluorescence in situ hybridisation (FISH). However, neither of these modalities is without limitations. Novel bright field in situ hybridisation techniques continue to provide viable alternatives to FISH testing. While these techniques are not limited to evaluation of the HER2 gene, the extensive number of studies comparing bright field in situ techniques with other methods of assessing HER2 status allow a robust evaluation of this approach. Analysis of the literature demonstrates that, when used to assess HER2 gene status, bright field in situ hybridisation demonstrates excellent concordance with FISH results. The average percentage agreement in an informal analysis of studies comparing HER2 amplification by chromogenic in situ hybridisation with FISH was 96% (SD 4%); κ coefficients ranged from 0.76 to 1.0. Although a much smaller number of studies are available for review, similar levels of concordance have been reported in studies comparing HER2 amplification by methods employing metallography (silver in situ hybridisation) with FISH. A summary of the advancements in bright field in situ hybridisation, with focus on those techniques with clinical applications of interest to the practicing pathologist, is presented.